Online Contact, Face-to-Face Contact, and Multilingualism: Young Swedish-Speaking Finns Develop Trilingual Identities. Issue 1 (1st January 2018) - Vincze, László; Joyce, Nick
Abstract : Based on the tenets of the social context model of second language acquisition, the present article examined the combined effect of online and face-to-face contact in developing multilingual skills and identities among young Swedish-speaking Finns (N = 304). The hypotheses were tested for Finnish as a second language and English as a third language using parallel models. The results were largely identical for both languages. Specifically, online contact enhanced language confidence which, in turn, contributed to language identity. However, online contact had a more substantial effect on confidence as well as identity among those who had little face-to-face contact with speakers of the given language. Findings and their implications are discussed.